A nucleic acid dependent chemical photocatalysis in live human cells - Arian, Dumitru; Cló, Emiliano; Gothelf, Kurt V.; Mokhir, Andriy (Chemistry - a European journal, 2010)
Only two nucleic acid directed chemical reactions that are compatible with live cells have been reported to date. Neither of these processes generate toxic species from nontoxic starting materials. Reactions of the latter type could be applied as gene-specific drugs, for example, in the treatment of cancer. We report here the first example of a chemical reaction that generates a cytotoxic drug from a nontoxic prodrug in the presence of a specific endogeneous ribonucleic acid in live mammalian cells. In this case, the prodrug is triplet oxygen and the drug is singlet oxygen. The key component of this reaction is an inert molecule (InP-2′-OMe-RNA/Q-2′-OMe-RNA; P: photosensitizer; Q: quencher), which becomes an active photosensitizer (InP-2′-OMe-RNA) in the presence of single-stranded nucleic acid targets. Upon irradiation with red light, the photosensitizer produces over 6000 equivalents of toxic singlet oxygen per nucleic acid target. This reaction is highly sequence specific. To detect the generation of singlet oxygen in live cells, we prepared a membrane-permeable and water-soluble fluorescent scavenger, a derivative of 2,5-diphenylisobenzofurane. The scavenger decomposes upon reaction with singlet oxygen and this is manifested in a decrease in the fluorescence intensity. This effect can be conveniently monitored by flow cytometry.
Zuerst veröffentlicht: 23 December 2009
Gesehen am 25.11.2022